Conventional technology and nanotechnology in wood preservation: A Review - Teck-Jin Teng; Mohamad Nasir Mat Arip; Kumar Sudesh; Anna Nemoikina; Zaihan Jalaludin; Eng-Poh Ng; Hooi-Ling Lee (BioResources)
Wood products are usually treated with wood preservatives to protect them from deterioration. Pressure or non-pressure preservative treatments can be utilized to incorporate biocide into the wood, depending on the applications of the end-products. Thermal and chemical modifications of wood represent alternative treatments that enhance the dimensional properties of wood and provide biological resistance. However, there is also a current trend to apply nanotechnology for wood preservation. Nanomaterials with unique properties can enhance the performance of wood preservatives, thereby increasing the service lifetime of the wood products. Nanotechnology can be applied for this purpose through impregnation of wood with a suspension of metallic nanoparticles, or through encapsulation of biocide with nanocarriers. Additionally, various nanomaterials also can be used in wood modification, especially coating treatment to provide superior service ability. Nevertheless, more studies are required to provide guidelines regarding the safety upon application of nanomaterials. This review will give an overview of current wood preservation techniques. Additionally, this paper examines current research on how nanotechnology is being applied for wood preservation.